Acute kidney injury after percutaneous nephrolithotomy for stones in solitary kidneys. (4th March 2017) - El-Nahas, Ahmed R.; Taha, Diaa-Eldin; Ali, Hussien M.; Elshal, Ahmed M.; Zahran, Mohamed H.; El-Tabey, Nasr A.; El-Assmy, Ahmed M.; Harraz, Ahmed M.; Moawad, Hazem E.; Othman, Mahmoud M.
Abstract: Objectives: The aim of this study was to report the incidence, severity, outcome and risk factors of acute kidney injury (AKI) following percutaneous nephrolithotomy (PNL) in solitary kidneys. Methods: The study included consecutive adult patients who underwent PNL for treatment of calculi in a solitary kidney between May 2012 and July 2015. Patients with congenital renal anomalies or with stages 4 and 5 chronic kidney disease (CKD) were excluded. Serum creatinine levels were measured the day before PNL, daily after PNL for 2–5 days and after 3 months. AKI was depicted according to changes in early postoperative serum creatinine levels and its severity was determined based on the Acute Kidney Injury Network (AKIN) classification. The outcome of AKI was evaluated after 3 months by changes in the stage of CKD. Univariate and multivariate statistical analyses were conducted to determine risk factors for developing AKI. Results: The study included 100 patients (62 males) with a mean ± SD age of 50 ± 11.7 years. Complications were reported for 27 patients. AKI developed in 25 patients; at the 3 month follow-up, 23 of them (92%) had completely recovered from AKI and two (8%) had developed stage 4 CKD. Independent risk factors for developing AKI were multiple PNL tracts and postoperative ureteric obstruction (relative risks were 14 and 22, respectively). Conclusions: The incidence of AKI was 25% after PNL for a solitary kidney. The likelihood of renal function recovery was 92%. Multiple PNL tracts and postoperative ureteric obstruction were risk factors for developing AKI.